Mechanical properties and tribological behaviour of electroless Ni–P–Cu coatings on corrosion-resistant alloys under ultrahigh contact stress with sprayed nanoparticles. (November 2019) - Meng, Maozhou; Leech, Andrew; Le, Huirong
Abstract: Threaded components manufactured from corrosion resistant alloys (CRA's) are vulnerable to galling. This paper develops a test matrix to systematically investigate the mechanical properties and tribological performance of electroless nickel phosphorous coatings on CRA's when subjected to high contact stress. Samples manufactured from 28Cr stainless steel were shot-peened for various periods prior to being electo/electroless coated. The coefficient of friction (CoF) of different coating systems was evaluated via sliding cross-pin method. Various wet and dry lubricants were utilised to examine tribological performance, furthermore the adhesion strength of the coatings was investigated by a bond and pull-off method. The study has shown a significant reduction in CoF for electroless nickel phosphorous coatings with prior shot-peening treatment and sprayed nanoparticles. Highlights: An electrolytic Ni layer is essential to achieve good adhesion of electroless coating on CRA. Electroless Ni–P and Ni–P–Cu coatings showed good tribological behaviour under ultrahigh stress. These coatings showed similar tribological behaviours, regardless of Cu content. Shot-peening enhanced tribological performance of the coatings in combination with nanoparticles. The electroless coatings were more wear resistant than exlectroplated Cu.